Industry Participation in India's Space Program: Current Trends and Perspectives for the Future. Issue 2 (1st September 2016) - Nagendra, Narayan Prasad
ABSTRACT: Over the past five decades, India has progressed to create one of the largest national space programs in the world, delivering space-based technology to solve the problems of man and society. The present work provides an overview of current trends regarding industry participation in the national space program of India. While insight into industry participation and upstream activity is provided in the space transportation and development of satellite systems, commercial aspects of satellite communication services, use of geospatial data, and navigation and timing services are addressed as a part of the downstream applications. Specific recommendations to expand the footprint of the participation of Indian industry in the utilization of space technology nationally with possible expansion internationally are provided herein for space program managers and policymakers for both the upstream and downstream activities.